2019
DOI: 10.1590/1806-9282.65.5.625
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of human papillomavirus and Pap test among Brazilian university students

Abstract: SUMMARY OBJECTIVE: Human papillomavirus (HPV) is the most prevalent sexually transmitted virus in the world and is associated with an increased risk of cervical cancer. The most effective approach to cervical cancer control continues to be screening through the preventive Papanicolaou test (Pap test). This study analyzes the knowledge of university students of health science programs as well as undergraduate courses in other areas of knowledge on important questions regarding HPV. METHOD: Four hundred and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
0
6
0
3
Order By: Relevance
“…A study carried out with 473 university students (Medicine, Nursing, Veterinary Medicine, Pharmacy, Dentistry, Biomedicine and Biology), as well as undergraduate courses in other areas of knowledge (Chemistry, Administration, Accounting, Computer Science and Mathematics) revealed that the Most students knew what the test was, as well as its frequency, however, 30.4% were unaware of the meaning of an altered result, that is, as the questions became more complex, the level of knowledge on the subject decreased. It is important to highlight that, when comparing the knowledge of students in the health field with students from other areas, it was observed that those in health presented greater knowledge (Baptista et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out with 473 university students (Medicine, Nursing, Veterinary Medicine, Pharmacy, Dentistry, Biomedicine and Biology), as well as undergraduate courses in other areas of knowledge (Chemistry, Administration, Accounting, Computer Science and Mathematics) revealed that the Most students knew what the test was, as well as its frequency, however, 30.4% were unaware of the meaning of an altered result, that is, as the questions became more complex, the level of knowledge on the subject decreased. It is important to highlight that, when comparing the knowledge of students in the health field with students from other areas, it was observed that those in health presented greater knowledge (Baptista et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One of the important reasons for this kind of behavior is that education of young people about reproductive health for now is not regulated by the system, and because of that the source of knowledge and information for young people are their peers, media as well as the internet. Research in relation to sexual behavior of students shows that students are a highrisk population for acquiring and transmitting STIs (7). Risky sexual behavior of students implies more frequent partner change, entering sexual relations under the effect of psychoactive substances, inconsistent condom use, etc.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, o câncer de colo de útero é o segundo tipo de câncer ginecológico mais comum, ficando atrás apenas do câncer de mama. Sendo também, o terceiro tipo de câncer mais comum em mulheres, excluindo o câncer de pele não melanoma 1 . Apesar da alta incidência e mortalidade, se configura como um câncer com possibilidade de prevenção, e com estratégias de prevenção consolidadas nas políticas de atenção a saúde.…”
Section: Introductionunclassified
“…infectadas pelo HPV tem quadros auto limitados que regridem espontaneamente depois de 12 a 30 meses, mesmo aquelas infectadas pelos de maior oncogênicidade como o tipo 16 e 181 . Ou seja, não é apenas a infecção pelo HPV que irá levar ao desenvolvimento do câncer, serão necessários fatores concomitantes para essa evolução, em especial medidas comportamentais para diminuir a infecção sexual pelo vírus.O câncer de colo irá surgir quando houver a infecção persistente pelo vírus HPV oncogênico, associado a fatores de risco.…”
unclassified